The tattoo and its relation with personal and social characteristics - Aragonés, Juan I. (Consorcio de Universidades Mexicanas A.C., 2016)
Tattooing is an increasingly frequent custom in western societies. This essay is an analysis of the existing connection between tattoos and several social and personal variables. The sample, comprising 189 people, of whom 65 were men, completed a questionnaire composed, firstly, of scales matching the Big Five personality factors, Need for Uniqueness, Sensation seeking, Self-esteem, Attitudes Toward Tattoos, and of sociodemographic and tattoo-related variables as well. The results show that women acquire tattoos more often than men, that the acquisition of a tattoo is more likely the more tattooed people are present in one’s daily life, and that those adopting a rather left-wing ideology are more inclined to have a tattoo. Moreover, Catholics acquire a significantly lower number of tattoos than atheists or agnostics, and there is a smaller presence of tattooed people in a person’s daily life the higher their educational level is. On the other hand, there is a significant association between having a tattoo and showing a higher score on Openness to experience, Need for Uniqueness, Self-esteem and Attitudes Toward Tattoos.